2-Fluoro-5-nitrophenyldiazonium: A Novel Sanger-Type Reagent for the Versatile Functionalization of Alcohols - Fischer, Oliver; Heinrich, Markus (Chemistry - A European Journal, 2021)
As a novel Sanger-type reagent, 2-fluoro-5-nitrophenyldiazonium tetrafluoroborate enabled the versatile functionalization of primary and secondary aliphatic alcohols. Based on a mild nucleophilic aromatic substitution of the fluorine atom under unprecedented, base-free conditions, the diazonium unit on the aromatic core of the resulting aryl-alkyl ether could be employed for such diverse transformations as radical C−H activation and cyclization, as well as palladium catalyzed cross-coupling reactions.
CRIS-Team Scopus Importer:2021-03-05
Keywords: C−C bond formation; C−H activation; diazonium; nucleophilic aromatic substitution; Sanger reagent

Cleavage of Organosolv Lignin to Phenols Using Nitrogen Monoxide and Hydrazine - Hofmann, Laura; Altmann, Lisa-Marie; Fischer, Oliver; Prusko, Lea; Xiao, Ganyuan; Westwood, Nicholas J.; Heinrich, Markus (ACS Omega, 2021)
From the variety of methods known for the depolymerization of organosolv lignin, a broad range of diversely substituted aromatic compounds are available today. In the present work, a novel two-step reaction sequence is reported, which is focused on the formation of phenols. While the first step of the depolymerization strategy comprises the 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ)-catalyzed oxidation of organosolv lignin with nitrogen monoxide so that two waste materials are combined, cleavage to the phenolic target compounds is achieved in the second step employing hydrazine and potassium hydroxide under Wolff-Kishner-type conditions. Besides the fact that the novel strategy proceeds via an untypical form of oxidized organosolv lignin, the two-step sequence is further able to provide phenols as cleavage products, which bear no substituent at the 4-position.
CRIS-Team Scopus Importer:2021-09-03

Identification and Quantification of Resveratrol and Its Derivatives in Franconian Wines by Comprehensive Liquid Chromatography-Tandem Mass Spectrometry - Hoferer, Laura; Rodrigues Guimarães Abreu, Vera Lúcia; Graßl, Fabian; Fischer, Oliver; Heinrich, Markus; Gensberger-Reigl, Sabrina (ACS Food Science & Technology, 2023)
Resveratrol and its derivatives are valued compounds in foods such as wine. To date, their occurrence and concentrations in Franconian wines are not known. Thus, the present study investigated resveratrol and its derivatives in Franconian wines. First, comprehensive ultrahigh-performance liquid chromatography (UHPLC)-tandem mass spectrometry methods were applied to identify cis-/trans-resveratrol, cis-/trans-piceid, deoxyrhapontigenin, trans-piceatannol, and cis-/trans-astringin. Second, a sensitive UHPLC-scheduled multiple reaction monitoring method for absolute quantification of the major resveratrol derivatives was developed, validated, and applied to 19 Franconian wine samples. Recovery rates ranged between 95.0 and 109.3% and reproducibility between 2.6 and 10.3%. The limits of detection/quantification were between 0.01 and 0.08 μg/mL. The samples contained 0.07-2.61 μg/mL cis-resveratrol, 0.05-3.82 μg/mL trans-resveratrol, 0.24-9.01 μg/mL cis-piceid, and 0.25-8.30 μg/mL trans-piceid. Additionally, the concentrations of deoxyrhapontigenin (0.02-0.53 μg/mL), trans-piceatannol (0.05-1.35 μg/mL), and trans-astringin (0.04-0.67 μg/mL) were quantified.
CRIS-Team Scopus Importer:2023-07-07
Keywords: piceid; precursor ion scan; resveratrol; scheduled multiple reaction monitoring; stilbene derivatives; UHPLC−MS/MS; wine

Medication safety in intravenous therapy: A compatibility study and analysis of reaction products of dihydralazine and metamizole - Koller, Anna Katharina; Fischer, Oliver; Krebs, Sabine; Heinrich, Markus; Dörje, Frank (Scientia Pharmaceutica, 2020)
The pharmacotherapy of critically ill patients is challenging due to the variety of drugs that have to be applied. As the majority of pharmaceuticals must be administered intravenously because of the critical condition of the patients, the compatibility of co-applied intravenous drugs is crucial for a safe and successful infusion therapy. Antihypertensive therapy was reported by health care professionals to be ineffective in association with concomitant application of dihydralazine and metamizole (dipyrone). As both drugs are administered in German intensive care units, we analyzed their compatibility, examined the mechanisms of underlying dihydralazine degradation, and identified reaction products of dihydralazine and metamizole. Binary combinations were prepared at the high and the low end of the nominal administration concentration. Validated high performance liquid chromatography/ultraviolet absorption (HPLC-UV) analysis was conducted to quantify drug amount and high performance liquid chromatography/mass spectrometry (HPLC-MS) was used to analyze degradation products. The combinations of dihydralazine and metamizole proved to be incompatible as dihydralazine concentration decreased immediately and considerably. Metamizole also slightly decreased over time. Specific degradation products of dihydralazine were identified and a degradation pathway was postulated. Our findings demonstrate that the intravenous co-administration of dihydralazine and metamizole should be strictly avoided due to the incompatibility of these two drugs.
CRIS-Team Scopus Importer:2020-06-02
Keywords: Dihydralazine; HPLC-MS; HPLC-UV; Infusion therapy; Medication safety; Metamizole; Y-site compatibility

Regiospecific Introduction of Halogens on the 2-Aminobiphenyl Subunit Leading to Highly Potent and Selective M3 Muscarinic Acetylcholine Receptor Antagonists and Weak Inverse Agonists - Fischer, Oliver; Hofmann, Josefa; Rampp, Hannelore; Kaindl, Jonas; Pratsch, Gerald; Bartuschat, Amelie; Taudte, Verena; Fromm, Martin; Hübner, Harald; Gmeiner, Peter; Heinrich, Markus (Journal of Medicinal Chemistry, 2020)
Muscarinic M-3 receptor antagonists and inverse agonists displaying high affinity and subtype selectivity over the antitarget M-2 are valuable pharmacological tools and may enable improved treatment of chronic obstructive pulmonary disease (COPD), asthma, or urinary incontinence. On the basis of known M-3 antagonists comprising a piperidine or quinuclidine unit attached to a biphenyl carbamate, S-fluoro substitution was responsible for M-3 subtype selectivity over M-2, while 3'-chloro substitution substantially increased affinity through a sigma-hole interaction. Resultantly, two piperidinyl- and two quinuclidinium-substituted biphenyl carbamates OFH243 (13n), OFH244 (13m), OFH3911 (14n), and OFH3912 (14m) were discovered, which display two-digit picomolar affinities with K-i values from 0.069 to 0.084 nM, as well as high selectivity over the M-2 subtype (46- to 68-fold). While weak inverse agonistic properties were determined for the biphenyl carbamates 13m and 13n, neutral antagonism was observed for 14m and 14n and tiotropium under identical assay conditions.
CRIS-Team WoS Importer:2020-05-15

Shifted Selectivity in Protonation Enables the Mild Deuteration of Arenes Through Catalytic Amounts of Bronsted Acids in Deuterated Methanol - Fischer, Oliver; Hubert, Anja; Heinrich, Markus (Journal of Organic Chemistry, 2020)
Taking advantage of the "differentiating effect" of the solvent methanol, deuterations of electron-rich aromatic systems can be carried out under mild acid catalysis and thus under far milder conditions than known so far. The exceptional functional group tolerance observed under the optimized conditions, which even includes highly acid-labile groups, results from a hitherto unexploited shifted selectivity in protonation, and enabled simple and straightforward access to complex deuterium-labeled compounds.
CRIS-Team WoS Importer:2020-10-23

Synthesis, Characterization, and Application of Muscarinergic M-3 Receptor Ligands Linked to Fluorescent Dyes - Köckenberger, Johannes; Fischer, Oliver; Konopa, Andreas; Bergwinkl, Sebastian; Mühlich, Susanne; Gmeiner, Peter; Kutta, Roger Jan; Hübner, Harald; Keller, Max; Heinrich, Markus (Journal of Medicinal Chemistry, 2022)
Through the linkage of two muscarinergic M-3 receptor ligands to fluorescent tetramethylrhodamine- and cyanine-S-type dyes, two novel tool compounds, OFH5503 and OFH611, have been developed. Based on the suitable binding properties and kinetics related to the M-3 subtype, both ligand-dye conjugates were found to be useful tools to determine binding affinities via flow cytometric measurements. In addition, confocal microscopy underlined the comparably low unspecific binding and the applicability for studying M-3 receptor expression in cells. Along with the proven usefulness regarding studies on the M-3, subtype, the conjugates OFH5503 and OFH611 could, due to their high affinity to the M-1 receptor, evolve as even more versatile tools in the field of research on muscarinergic receptors.
CRIS-Team WoS Importer:2023-01-06